20 years Journal of Special Education and Rehabilitation - a period of continuous development - Trajkovski, Vladimir; Donev, Doncho (Faculty of Philosophy, UKIM, Skopje, Macedonia, 2017)
Introduction and goal: The first edition of the “Journal of Special Education and Rehabilitation” was released for the first time in 1997, and over the past 20 years, 37 issues have been published. In the Journal different kinds of articles are published from several scientific disciplines such as special education and rehabilitation, medicine, pedagogy, psychology, social politics, law and others. The goal of this editorial is to review the 20 years’ existence of the “Journal of Special Education and Rehabilitation” and to point out the future activities for the promotion of the quality of published articles and the integrity and visibility of the journal. Methods: Review and analysis of the documentation of the journal as well as the evidence of submitted, rejected and accepted manuscripts, the structure of published articles by according to their uniqueness, and other specific moments in the development of the journal from its founding in 1997 – and especially the achievements in the period from 2008 to 2016. Results: Over the past nine years we have noticed a growth in the number of authors and co-authors from the published articles by 358, from 28 different countries. The rate of acceptance of new articles has reduced from the original 93% in the first years of the foundation of the journal to 33% in the last three years. The majority of published articles come from authors from Macedonia which we can find in 31 articles or 27.7% from the overall published articles. The majority of authors have published original manuscripts (n= 87 or 53%), and then we have 12% articles of revision and 11.5% scientific articles. With regard to the different sections of the journal, the most published are news and information that are not subject to review (28%) while from the articles that are reviewed the most represented section is from special education and rehabilitation with a total of 16.5% from the overall number of published articles. Conclusion: The “Journal of Special Education and Rehabilitation” is a journal that undertakes review on its articles and has an open access policy, which marks a continuous progress in quality and visibility with an appointed goal to serve as a solid medium to enhance scientific research and to promote professional achievements in the field of special education and rehabilitation and the similar fields in biomedicine in the Republic of Macedonia and abroad.
20 години Дефектолошка теорија и практика - период на континуиран развој
Keywords: Journal of Special Education and Rehabilitation, 20 years, reviewed journal, open access, publishing ethics and integrity